An Investigation into the Effect of Materials on Joining for Automotive Panel Using Tailor Welded Blanks - N. M. Zuki, N. M.; M. M., Rahman; M. M., Noor; K., Kadirgama; M. R. M., Rejab (2008)
A laser welded blank for use in applications calling for tailor welded blank (TWB) in vehicle panel assemblies. A promising approach to reduce manufacturing costs, decrease vehicle weight, and improve the quality of automotive body components is through the use of tailor-welded blanks. This term refers to blanks where multiple sheets of material are welded together to create a single blank prior to the forming process. The welding process creates formability concerns in a traditional forming process due to material property changes in the weld and in the heat-affected zone adjacent to the weld. Malaysian automotive manufacturers are still lack of this advancement. Hence, this project endeavors to build a platform for the industries by pioneering researches in this area. This paper presents to investigate the weld properties of high strength steel laser weld for joining the automotive panel. Laser weld and different types of steel are considered in this study. Experiment was carried out to determine the properties of materials after welding, forming and drawing process of TWB. It is observed from the acquired results that the potential TWB gives the best material combination. It can be seen that cross sectional area and steel grade are the most significant subjected to the tensile loading.